CONTEMPORARY RACISM IN ENGLAND AND THE CASE OF REFUGEE CHILDREN - Liana Lewis (Estudos de Sociologia)
In contemporary England refugeeness has been one of the main issues throughout de British identity has been imagined. The article seeks to analyse how in this context of forced migration racism has been acquiring a new pattern that goes beyond the black/white dualism, although such a dynamic still plays an important role on the way groups of people have been othered.